A Further Supplement to an Act Entitled “An Act to Prevent the Use of Fire-arms by Free Negroes and Free Mulattoes and for Other Purposes, § 1, 9 Del. Laws 552 (1843) - (:unkn) unknown (General Publisher, 1843)
Repealed laws allowing the Justice of the Peace to license or permit a “free negro or free mulatto” to have, use, or possess a gun or fowling piece.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES